PENGARUH LATIHAN LOMPAT GAWANG DAN LATIHAN LOMPAT SAMPING TERHADAP KEMAMPUAN HEADING BOLA PADA PERMAINAN SEPAKBOLA DITINJAU DARI DAYA LEDAK OTOT TUNGKAI - Palmizal, Palmizal; Nurkadri, Nurkadri; Pratama, Budiman Agung (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This research is a field experimental study with a 2 x 2 factorial design. The population is all students of the Faculty of Sport Science, Jambi State University with SportsTraining Education samples with a sampling technique is a proportional sampling of 40 people. The data analysis technique used is Analysis of Variance (ANAVA) at a significant level of 95%. By looking at the existing problems, the results obtained from the data processing shows that: there is no significant difference in effect between hurdles and side jump exercises on the ability of heading balls in football (Fo = 0.939> Ft = 4.11). There is a significant difference between the power of high limb muscle explosions with low limb muscle explosiveness to the ability of heading balls in football (Fo = 17,976> Ft = 4.11). For athletes who have high leg muscle explosive power, there is a significant difference in effect between goal jump training and side lomato training on ball heading abilities in football (to = 6.034> tt = 1.73). For athletes who have low leg muscle explosive power, there is a significant difference in effect between hurdles and side jump exercises on heading ball abilities in football (to = 12,357> tt = 1.73).